Cardiovascular English - Ribes, Ramón. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
After the successful publication of Medical English, Radiological English and Primary Care English by Springer, I considered it a top priority to keep on writing medical English books by specialties, which could become useful tools for health care professionals and medical students all over the world. Being a cardiovascular radiologist myself, Cardiovascular English was one of the first titles that came to my mind when I began to think about a series of medical English books by specialties. In spite of the fact that c- diovascular diseases are my main area of interest, I would not have dared co-write a book on cardiovascular English without the enthusiastic support of Dr. Mejía. This book project started in Benalmadena when, during the dinner after a 1-day course on cardiovascular imaging, Dr. Manuel Concha, a pro- nent figure in cardiac surgery and one of the pioneers of cardiac tra- plants in my country, and who was aware of my idea of writing a card- vascular English book, introduced Dr. Mejía to me saying “Ramón, Sergio is the person you are looking for.” He was absolutely right. Sergio Mejía has been enthusiastically c- mitted to the book project since its inception. Like its predecessors, Cardiovascular English is not written by English teachers and aimed at English students, but it is written by doctors and aimed at doctors.